Doubly stochastic (pseudo)gene expression in the regulation of cancer. (14th August 2017) - Petrosyan, K G; Hu, Chin-Kun
Abstract: We extend a model of the regulation of cancer by gene and pseudogene messenger RNAs to take into account cell-to-cell variability. This introduces an additional randomness to the intensity of the intracellular noise. The intracellular stochasticity is modelled via an additive white noise source and the intercellular stochasticity, or randomness, is modelled via a steady-state Γ -distribution for the intracellular noise intensity. The doubly stochastic process is treated numerically and displays a difference compared with the single stochastic (pseudo)gene expression process, which is the randomness-induced shift of the onset of even–odd oscillations in the number of molecules. Similarities to experimental outcomes in the related literature are pointed out.